Self-Esteem, Failure Feedback, and Physiological Reactivity: Implications for Working Memory and Aggression - Ryan, John Patrick (2009)
Research has recently begun to focus on separable conscious and subconscious aspects of self-esteem. Meanwhile, research on aggressive behavior has found that some individuals with high self-esteem are more prone to aggressive behavior. Based on a biopsychosocial approach, research has shown that appraisals of threat/challenge are marked by distinct physiological responses – threat appraisals are marked by activation of the hypothalamic-pituitary-adrenal axis, whereas challenge appraisals are marked by activation of the sympathetic adrenal-medullary axis. The present study examines the relationship between failure feedback, implicit and explicit self-esteem, appraisals, working memory and aggression in a series of three experiments. Experiment 1 examined the impact of failure feedback on stress physiology and found that individuals who displayed a physiological response to failure feedback consistent with a challenge response, as indicated by an increase in blood pressure without a concurrent increase in salivary cortisol, were the most likely group to become aggressive. Experiment 2 examined the relationships between implicit and explicit self-esteem in predicting aggressive behavior. Implicit self-esteem predicted behavioral inhibition in response to negative feedback such that higher implicit self-esteem was associated with fewer behavioral inhibition errors. In Experiment 3, threat/challenge motivations were manipulated to determine their impact on working memory performance. Increases in feelings of threat were associated with greater working memory performance, whereas increases in feelings of challenge were associated with decreases in working memory performance. The present study is the first to examine aggression in the context of threat/challenge appraisal responses. Overall, this study suggests that appraisals and physiology can assist in predicting aggressive behavior, although the cognitive mechanism by which this occurs remains elusive